STRATEGIC MANAGEMENT OF ENTERPRISES IN THE CONTEXT OF DIGITAL TRANSFORMATION - Hikmatulloyeva Zuxra Mirxon qizi (International Journal of Literature and Language Studies, 2026)
This article analyzes the issues of strategic management of enterprises in the context of digital transformation. The impact of digital technologies on enterprise activities, their role in the strategic management process, and their significance in enhancing the competitiveness of enterprises are examined. Furthermore, the opportunities and challenges arising in the process of digital transformation are analyzed, and proposals for overcoming them are presented. Within the scope of the study, the strengths and weaknesses of enterprises, existing opportunities, and potential threats are assessed based on a SWOT analysis.